STUDENTS’ATTITUDES TOWARD DISABILITY - Dibra, Gezim; Osmanaga, Fatbardha; Bushati, Jozef (European Scientific Journal, ESJ, 2013)
Students’attitudes toward disability are important, because, young people, and, in ithis context, the students represent the future of the country and their attitudes toward disability affect the process of social integration of disabled people. For the realization of this study it is used the technique of questionaire. The measuring instrument is the SADP (Scale of Attitudes Toward Disabled Persons) scale to measure students’ attitudes. The questionnaire is fulfilled from students of the Faculty of Educational Sciences and Faculty of Economics. The paper aims to measure the mean attitude scores on the SADP scale of students of these faculties of the University “Luigj Gurakuqi” of Shkodër city. The aper aims, also, to analyze the impact of specific academic programme on mean SADP score of students. The data collected from the questionnaires was analyzed by means of the SPSS program, variant 20. It is used the analysis of variance Anova table and eta to examine the impact of specific academic programme on students’attitude toward disability. There are given the appropriate conclusions. The attitude of students of the Faculty of Educational Sciences and Faculty of Economics toward disability is favourable. The type of the specific academic programme doesn’t impact their attitude toward disability. The students have positive opinion about the capability of disable individuals to adjust to a life outside an institutional setting. The students think that disabled people should have the opportunity for gainful employment and that they should have equal employment opportunities. The students haven’t positive opinion about the integration of disabled children in schoool.